Badges and Brothels: Police Officers' Attitudes Toward Prostitution - Jorgensen, Cody (Frontiers in Sociology, 2018)
There is a gap in the literature regarding police officers’ attitudes about vice, specifically prostitution. Scholars should study this topic because police are interacting with drug dealers and drug users, prostitutes and Johns, and gamblers and bookies regularlyon a day to day basis. Additionally, how police perceive prostitution is likely to influence how they enforce laws prohibiting it. This paper presents survey items measuring police officers’ attitudes about prostitution related offenses and examines the relationships between officers’ attitudes towards prostitution and their personal as well as professional characteristics. Responding officers displayed fairly serious and punitive attitudes toward prostitution offenses. Respondents believed that prostitution was a serious problem in their city and that it leads to more serious crimes. Demographic characteristics of officers such as age, gender, political ideology, and education had more influence on prostitution attitudes than police characteristics such as experience with the vice/narcotics unit. Policy implications derived from the findings are discussed.